Assessment of lactic acid bacteria isolated from fermented Bambangan as probiotic and the adhesion properties of the selected strains - Ng, Seah Young (2018)
Probiotics are continuously gaining attention in the food industry for the development of functional foods due to their ability to confer several health benefits to the hosts. The study aims to elucidate the probiotic properties and the underlying adhesion mechanisms of lactic acid bacteria (LAB) isolated from an indigenous fermentation of Bambangan (Mangifera pajang). The isolated LAB were confirmed their identities by analyzing their 16S rRNA gene sequences and their probiotic properties were evaluated by a series of in vitro assay s. The selected probiotic candidates were further investigated for their cell surface proteinaceous components in adhesion to the human CaCo-2 cell line and the corresponding surface proteins were identified. The main species of the LAB isolated from fermented Bambangan were identified as Ladobacillus plantarum and Lactobacillus brevis. Approximately 4 3% of the identified LAB strains displayed excellent survival at pH 3.0 with at least 6 log CFU/ml for 4 hours and able to withstand 2.0% bile salt. Interestingly, the LAB challenged in simulated intestine juice showed 2 fold increment in viability when pepsin is present at pH 2.0 compared to those without addition of pepsin. Besides, a high aggregation activity (>20%) was found in most of the LAB strains. They also exhibited great antibacterial activity against pathogenic bacteria such as Listeria monocytogenes, Salmonella Typhimurium, Salmonella Enteritidis and Yersina enterocolitica. The eight selected probiotic candidates were found comparable to the commercial strain of Lactobacillus acidophilus LAOS on probiotic properties. Most of them were tolerable to 60°C for 10 minutes with at least 70% viability and 4 strains were tolerant up to 6% sodium chloride. No probiotic candidate possesses any unusual resistance towards antibiotics; neither produces biogenic amines nor gives cytotoxic effect to the intestinal cells. Among all the tested probiotic candidates, L. plantarum 0612 shows the highest adhesion percentage ( 5.51 %) to the human colon epithelial cells (Caco-2). However, the adhesion of L. plantarum 0612 to Caco-2 cells has reduced by 70% upon treatment with lithium chloride, indicating the involvement of cell surface proteinaceous components in the adhesion. The cell surface proteins of L. plantarum 0612 were fractionated into 8 fractions by using anion exchange chromatography. The fractions were incubated in Caco-2 cells, followed by adhering L. plantarum 0612 to the respective Caco-2 cells. Results showed fraction-7 has significantly reduced the adhesion of L. plantarum 0612 onto the Caco-2 cells as compared to other protein fractions. The cell surface proteins ( fraction-7) that bound to the Caco-2 cells were recovered and the SOS-PAGE revealed that 5 protein bands with molecular weight from 25 kDa to 65 kDa are most likely responsible in the adhesion of L plantarum 0612 to Caco-2 cells. The protein bands have been identified as serine/threonine protein kinase, D-alanine - D-alanine ligase, NADP-dependent malic enzyme, and 2 uncharacterized proteins, which could be novel adhesive proteins. In conclusion, 6 strains of L plantarum (0123, 0140, 0147, 0157, 0611 and 0612) and 2 strains of L brevis (0808, 0871) could be used as probiotic candidates in food and therapeutic applications. L. plantarum 0612 is the most promising probiotic bacteria that highly adhesive to the human intestinal cells due to the presence of multiple cell surface associated proteins and novel proteins.